KALIMAT â€“ KALIMAT MINOR DALAM FILM MR. & MRS. SMITH KARYA DOUG LIMAN - Omas, Gabriella Nafiri (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Language is always related with human. Therefore, to learn more about language is very important to us. Linguistics is the study of language. The study of patterns to make sentences is syntax. This study is entitled â€œKalimat â€“ kalimat Minor dalam Film Mr. & Mrs. Smith Karya Doug Limanâ€. The writer used the theory of Charless Hockett (1958) to identify and analyze the data that have been found in the film. According to Hockett, minor sentence is not complete sentence. There are four types of minor sentence, subjectless minor sentence, vocative minor sentence, aphoristic minor sentence and fragmen minor sentence which are sub categorized into three parts, they are completive fragmen minor sentence, special completive fragmen minor sentence and exclamatory minor sentence. The result of this research shows that there are only three types of minor sentence in the film, such as subjectless minor sentence, vocative minor sentence and fragmen minor sentence. This study is expected to provide more information about minor sentence to the readers.